Proteinuria in dogs with gallbladder mucocele formation: A retrospective case control study. (6th February 2021) - Lindaberry, Crystal; Vaden, Shelly; Aicher, Kathleen M.; Seiler, Gabriela; Robertson, James; Cianciolo, Rachel; Yang, Ching; Gookin, Jody L.
Abstract: Background: Proteinuria is an independent risk factor for morbidity and mortality in dogs. An association between proteinuria and gallbladder mucocele formation in dogs is unknown. Objective: Determine if gallbladder mucocele formation or clinicopathologic comorbidities are associated with proteinuria. Animals: Twenty‐five dogs with mucocele formation and 25 breed and age‐matched control dogs from a prior study. Methods: Retrospective case control study. Proteinuria defined by calculated urine dipstick protein concentration (mg/mL) to urine specific gravity (USG) ratio. Clinicopathologic findings, postcosyntropin cortisol concentration, thyroid function profile, and illness severity score were recorded. Results: Median urine dipstick protein concentration to USG ratio and number of dogs having a ratio ≥1.5 were significantly higher for dogs with mucocele formation compared to control dogs. Proteinuria was not significantly associated with CBC or serum biochemistry profile abnormalities but increased in relation to severity of illness. Conclusions and Clinical Importance: Gallbladder mucocele formation is significantly associated with proteinuria in dogs. Diagnosis and treatment of proteinuria in dogs with mucocele formation might minimize long term kidney morbidity in these patients.